2016
DOI: 10.18677/enciclopedia_biosfera_2016_114
|View full text |Cite
|
Sign up to set email alerts
|

SUPERAÇÃO DE DORMÊNCIA TEGUMENTAR DE SEMENTES DA PATA DE VACA (Bauhinia forficata Link)

Abstract: RESUMOA espécie Bauhinia forficata Link. apresenta rápido crescimento e altas taxas de sobrevivência no campo, no entanto, suas sementes apresentam desuniformidades na germinação, sendo esta característica desfavorável para produção de mudas em viveiros florestais. Nesse sentido, objetivou-se identificar métodos para superar a dormência, promovendo a germinação e o vigor de sementes da espécie B. forficata Link. As sementes foram colhidas da área do Horto Medicinal, localizado no município de Botucatu, e subme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…For other forest species, immersion in H2SO4 was also not efficient for overcoming seed dormancy. As in the cases of Bauhinia forficata (Ronchi et al, 2016); Schizolobium parahyba (Candido e Oliveira, 2018); ofAcacia mangium (Fernandes et al, 2018); and ofSchizolobium amazonicum (Carvalho et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For other forest species, immersion in H2SO4 was also not efficient for overcoming seed dormancy. As in the cases of Bauhinia forficata (Ronchi et al, 2016); Schizolobium parahyba (Candido e Oliveira, 2018); ofAcacia mangium (Fernandes et al, 2018); and ofSchizolobium amazonicum (Carvalho et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…1A) [22,23]. In relation to the imbibition in water at 80ºC (T5), it can be inferred that this probably caused the death of the embryo at the end of the experiment, was observed that the seeds were deteriorated, what caused a soft and rotted tegument, since under abiotic stress reactive oxygen species are formed and cause oxidative damages to many cellular components like cell wall and cell membranes, what could explain the embryo death [22][23][24][25][26].…”
Section: Seed Coat Ormancy Overcomementioning
confidence: 99%
“…Sementes que não foram imersas em ácido apresentaram o menor valor de condutividade (147,53 µS cm -1 g -1 ) em função de não haver danos ao tegumento da semente. Resultados semelhantes foram observados em Bauhinia forficata Link, em que a imersão das sementes em ácido sulfúrico por 5 minutos proporcionou o maior valor de condutividade elétrica em relação à testemunha sem superação de dormência e aos demais tratamentos (RONCHI et al, 2016).…”
Section: Escarificação Químicaunclassified